Five-Year Trends in Payments for Neurologist-Prescribed Drugs in Medicare Part D. (20th April 2021) - de Havenon, Adam; Delic, Alen; Dehoney, Sarah; Whetman, Presley; Sheibani, Nazanin; Callaghan, Brian; Ney, John; Esper, Gregory J.; Magliocco, Brandon; Nair, Kavita V.
Abstract : Objective: To determine whether there was an increase in payments for neurologist-prescribed drugs, we performed a retrospective analysis of prescription claims in the Medicare Part D Prescriber Public Use Files from 2013 to 2017. Methods: We included claims prescribed by providers with the taxonomy "neurology" and included drugs present in all 5 years. Drugs were designated in 2013 as generic (GEN), brand name only (BNO), and brand name prescribed even though a generic equivalent is available (BNGE). To observe payment trends, the percentage change in the per claim payment was compared between drug classes. Results: We included 520 drugs, of which 322 were GEN, 61 were BNO, and 137 were BNGE, representing 90, 716, 536 claims and generating payments of 26, 654, 750, 720. While the number of claims from 2013 to 2017 increased only 7.6%, the total payment increased 50.4%. Adjusted for inflation, claim payments for GEN drug increased 0.6%, compared to significant increases in BNO and BNGE drugs of 42.4% and 45.0% ( p trend < 0.001). The percentage of overall GEN claims increased from 81.9% to 88.0%, BNO increased from 4.9% to 6.2%, and BNGE decreased from 13.3% to 5.8%. Neuroimmunology/multiple sclerosis drugs represented >50% of the total payments despite being only 4.3% of claims. Conclusions: Payments for neurologist-prescribed brand name, but not generic, drugs in Medicare Part D increased consistently and well above inflation from 2013 to 2017. Unless the overall trend stabilizes or is reversed or high cost-to-claim drugs are addressed, this trend will place an increasing burden on the neurologic Medicare budget.